Trace phase detection and strain characterization from serial X-ray free-electron laser crystallography of a Pr0.5Ca0.5MnO3 powder. (17th November 2014) - Beyerlein, Kenneth R.; Jooss, Christian; Barty, Anton; Bean, Richard; Boutet, Sébastien; Dhesi, Sarnjeet S.; Doak, R. Bruce; Först, Michael; Galli, Lorenzo; Kirian, Richard A.; Kozak, Joseph; Lang, Michael; et al.
Abstract : We report on the analysis of virtual powder-diffraction patterns from serial femtosecond crystallography (SFX) data collected at an X-ray free-electron laser. Different approaches to binning and normalizing these patterns are discussed with respect to the microstructural characteristics which each highlights. Analysis of SFX data from a powder of Pr0.5 Ca0.5 MnO3 in this way finds evidence of other trace phases in its microstructure which was not detectable in a standard powder-diffraction measurement. Furthermore, a comparison between two virtual powder pattern integration strategies is shown to yield different diffraction peak broadening, indicating sensitivity to different types of microstrain. This paper is a first step in developing new data analysis methods for microstructure characterization from serial crystallography data.